RBSP3 (HYA22) is a tumor suppressor gene implicated in major epithelial malignancies - Kashuba, Vladimir I. (National Academy of Sciences, 2004)
Chromosome 3p21.3 region is frequently (>90%) deleted in lung and other major human carcinomas. We subdivided 3p21.3 into LUCA and AP20 subregions and discovered frequent homozygous deletions (10-18%) in both subregions. This finding strongly implies that they harbor multiple tumor suppressor genes involved in the origin and/or development of major epithelial cancers. In this study, we performed an initial analysis of RBSP3/HYA22, a candidate tumor suppressor genes located in the AP20 region. Two sequence splice variants of RBSP3/HYA22 (A and B) were identified, and we provide evidence for their tumor suppressor function. By sequence analysis RBSP3/HYA22 belongs to a gene family of small C-terminal domain phosphatases that may control the RNA polymerase II transcription machinery. Expression of the gene was drastically (>20-fold) decreased in 11 of 12 analyzed carcinoma cell lines and in three of eight tumor biopsies. We report missense and nonsense mutations in tumors where RBSP3/HYA22 was expressed, growth suppression with regulated transgenes in culture, suppression of tumor formation in severe combined immunodeficient mice, and dephosphorylation of ppRB by RBSP3/HYA22, presumably leading to a block of the cell cycle at the G(1)/S boundary.